Before you know kindness : a novel - Bohjalian, Chris, 1962- (New York : Vintage contemporaries, 2005)
On a balmy July night in New Hampshire a shot rings out in a garden, and a man falls to the ground, terribly wounded. The wounded man is Spencer McCullough, the shot that hit him was fired (accidentally?) by his adolescent daughter Charlotte. It's a family saga that is timely in its examination of some of the most important issues of our era, and timeless in its exploration of the strange and unexpected places where we find love.
Keywords: Gunshot wounds -- Patients -- Fiction; Animal rights activists -- Fiction; Parent and child -- Fiction; Hunters -- Fiction; Psychological fiction; Domestic fiction; Manhattan (New York, N.Y.) -- Fiction; Vermont -- Fiction